Kajian Teoritis Pengaruh Jenis Material Dieletrik Terhadap Penurunan Tegangan Listrik Kapasitor - Jaya, Gede Wiratma; Aponno, Sanny Virginia; Barus, Carolina Sri Athena (UNIVERSITAS INDRAPRASTA PGRI, 2024)
This study examines the influence of the dielectric constant of various types of materials, such as activated carbon, chicken fat, and polyester knitted fabric, on the decrease in capacitor voltage within a series resistor-capacitor (RC) circuit using a theoretical approach. Based on the research results, it is shown that to decrease the voltage value from 12 Volts to near 0 Volts, each dielectric material requires a different time in microsecond (s) or 10-6 seconds. The time required for the electric voltage of the capacitor to decrease from 12 Volts to 6 Volts (50%) for each dielectric, such as activated carbon, chicken fat, and polyester knitted fabric are 73.56 microsecond, 222.80 microsecond, and 294.93 microsecond, respectively. The decrease in voltage caused by the discharge of electric charge from a capacitor over time depends on the choice of dielectric material used. This is because the compound composition and morphological structure of the materials fibers significantly influence the dielectric constant value, which is directly proportional to the decrease in electrical voltage. Therefore, a capacitors ability to maintain a certain capacitance over a specific period is in accordance with its utilization needs in an electrical circuit.